Implikasi Pendidikan Karakter dalam Novel Lelaki Pembawa Kain Kafan Karya Griven H. Putera - Septiana, Vonica; Shomary, Sudirman (UIR Press, 2024)
Character education plays an integral part in shaping human personality and behavior, with its values often found in literary works. Literature serves not only as a form of entertainment but also as a platform for conveying deep moral and ethical values. This research examines the values of character education in the novel